Insuring educational risk: opportunities versus income - Dirk Schindler; Benjamin Weigert (Center for Economic Studies and ifo Institute (CESifo), 2008)
We develop a model of education where individuals face educational risk. Successfully entering the skilled labor sector depends on individual effort in education and public resources, but educational risk still causes (income) inequality. We show that an optimal public policy consists of deferred skill-specific tuition fees, lump-sum transfers/taxes, and public funding of the educational sector. We argue that improved educational opportunities matter more than direct income transfers in a Second-best setting. Contrary to standard models of income risk, it is not optimal to use a proportional wage tax, because combining skill-specific tuition fees and public education spending provide both insurance and redistribution at lower costs. A wage tax is only optimal if skill-specific tuition fees are not available.
Keywords: H21; I2; J2; 330; Human capital investment; endogenous risk; learning effort; optimal taxation; public education; Bildungspolitik; Bildungsinvestition; Risiko; Bildungsverhalten; Optimale Besteuerung; Bildungschancen; Öffentliche Bildungsausgaben; Theorie